Reduced efficiency of sarcolipin‐dependent respiration in myocytes from humans with severe obesity - Paran, Christopher W.; Verkerke, Anthony R.P.; Heden, Timothy D.; Park, Sanghee; Zou, Kai; Lawson, Heather A.; Song, Haowei; Turk, John; Houmard, Joseph A.; Funai, Katsuhiko (Obesity (Silver Spring, Md.), 2015)
Objective Sarcolipin (SLN) regulates muscle energy expenditure through its action on sarco/endoplasmic reticulum Ca2+‐ATPase (SERCA) pump. It is unknown whether SLN‐dependent respiration has relevance to human obesity, but whole‐transcriptome gene expression profiling revealed that SLN was more highly expressed in myocytes from individuals with severe obesity (OB) than in lean controls (LN). The purpose of this study was to examine SLN‐dependent cellular respiratory rates in LN and OB human muscles. Methods Primary myocytes were isolated from muscle biopsy from seven LN and OB Caucasian females. Cellular respiration was assessed with and without lentivirus‐mediated SLN knockdown in LN and OB myocytes. Results SLN mRNA and protein abundance was greater in OB compared to LN cells. Despite elevated SLN levels in wild‐type OB cells, respiratory rates among SLN‐deficient cells were higher in OB compared to LN. Obesity‐induced reduction in efficiency of SLN‐dependent respiration was associated with altered sarcoplasmic reticulum phospholipidome. Conclusions SLN‐dependent respiration is reduced in muscles from humans with severe obesity compared to lean controls. Identification of the molecular mechanism that affects SLN efficiency might lead to interventions that promote an increase in skeletal muscle energy expenditure.